DATA COLONIALISM AND DATA SOVEREIGNTY IN INDIGENOUS SPACES - Cocq, Coppélie (AoIR Selected Papers of Internet Research, 2023)
This paper will discuss a topic of prioritized importance in contemporary Indigenous research: data sovereignty. In the light of the historical and cultural contexts in which we conduct our research, we need to drastically question and decenter research practices that could contribute to reiterating, maintaining, and amplifying colonial practices and perspectives. Data harvesting is such a practice, and an issue of immediate interest on the agenda of Indigenous researchers and allies. Efforts toward ethically valid and cultural-sensitive modes of data use are taking shape in Indigenous research, calling for an increased awareness about the topic among scholars within the interdisciplinary field of digital research. This presentation takes its point of departure in Sápmi, the traditional area of settlement of the Indigenous Sámi people, and in ongoing research and initiatives in the area. The international research context constitutes the framework for contextualizing topical debates and issues in Sápmi. First, I will approach and examine practices and principles of data collection, data management and data curation through the lens of Indigenous research. Second, I will discuss examples of digital initiatives in curatorship of Indigenous traditional knowledge, for instance the labelling of cultural heritage, use of metadata and access to library and archive collections. Current debates and ongoing works about ethical guidelines and about the application of FAIR and CARE principles will be central in this discussion.